PELATIHAN STRATEGI PEMASARAN YANG DIGERAKKAN OLEH PELANGGAN PADA UKM - Rodhiah; Mahanani, Zenita Dian; Rosyada, Maulin Amrina (Transpublika Publisher, 2023)
The challenge in marketing is to identify potentially profitable markets to serve. SMEs need to identify who the potential market segments are to become their target market. Through a segmentation strategy, the owner will be better prepared and focused on providing services to its customers. The objective of the PKM activity is to provide training to SMEs on customer-driven marketing strategies. The partner chosen for the activity is engaged in a flower craft business located in Serang, Banten province. The activity method involves conducting online training through Zoom meetings, presented in the form of a PowerPoint presentation, covering topics such as market segmentation, target market determination, differentiation, and positioning. The results of the activity went smoothly, with partners enthusiastic about receiving the presented material. Through this activity, it is hoped that partner understanding will be enhanced to effectively implement customer-driven marketing strategies.